2012
DOI: 10.3126/jcmsn.v8i1.6828
|View full text |Cite
|
Sign up to set email alerts
|

Management of haemangioma neck using sclerosing agent- a case report

Abstract: Although hemangiomas are common in infancy and childhood, they are probably developmental abnormalities rather than true neoplasms. In present case we have treated a child aged 10 years with haemangioma of the right side of the Neck. After thorough investigation we posted this for intralesional infiltration of Sclerosing agent (Inj. Polidocanol 3%) in 1:3 dilution with normal saline. Approximately 2 ml Inj. Polidocanol diluted with saline was injected into the lesion. And the same procedure was repeated in thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The results of the actual study were similar to the data of literature relating to sclerotherapy, with variations according to the type of sclerosing agent, its concentration, the number of injections, and the intervals between each treatment session [13, 14, 18, 24, 29, 30]. …”
Section: Discussionsupporting
confidence: 76%
“…The results of the actual study were similar to the data of literature relating to sclerotherapy, with variations according to the type of sclerosing agent, its concentration, the number of injections, and the intervals between each treatment session [13, 14, 18, 24, 29, 30]. …”
Section: Discussionsupporting
confidence: 76%
“…3 Bhadoria et al have reported a case where they injected Polidocanol after diluting it with normal saline and observed regression with no complications. 10 In our study we did not dilute the drug.…”
Section: Discussionmentioning
confidence: 96%